The Small GTPase Ral orchestrates MVB biogenesis and exosome secretion. (2nd November 2018) - Hyenne, Vincent; Labouesse, Michel; Goetz, Jacky G.
ABSTRACT: Extracellular vesicles are novel mediators of cell-cell communication. They are present in all species and involved in physiological and pathological processes. One class of extracellular vesicles, the exosomes, originate from an endosomal compartment, the MultiVesicular Body (MVB), and are released from the cell upon fusion of the MVB with the plasma membrane. Although different molecular mechanisms have been associated with MVB biogenesis and exosome secretion, how they coordinate remains poorly documented. We recently found that the small GTPase Ral contributes to exosome release in nematodes and mammalian tumor cells. More specifically, we found that C. elegans RAL-1 is required for the biogenesis of MVBs, and later for MVB fusion with the plasma membrane. Here, we discuss our results in relationship with other factors involved in extracellular vesicle production such as the ESCRT complex and Phospholipase 1D. We propose models to explain Ral function in exosome secretion, its conservation in animals, and its possible role in tumor progression.